PENYELESAIAN KASUS GHARAWAIN (MASALAH TSULUTS AL-BAQI DALAM WARISAN) - M Zuhdi (Program Studi Hukum Keluarga Islam, 2023)
Gharawain, tasniyah form of lafadz gharr (brilliant star). So called because his fame is like a shining star. Another name for gharawain is Umariyatain because the way to solve it was introduced by Umar bin Khattab r.a. The gharawain problem is a form of inheritance problem that was decided by Umar and accepted by the majority of his friends and followed by the majority of scholars. This problem occurs when adding up several furudhs in one inheritance case where the results are not satisfactory to some of the mothers and fathers. If they jointly inherit with no other heirs, then the mother receives 1/3 and the father receives the ashabah. The basic principle is that the mother receives 1/3 and the father 2/3, in other words the male share is double that of the female. This situation still applies when the mother and father are together with the heirs of the husband or wife. So after the husband or wife's share is given, the mother receives 1/3 and the father receives the rest. Keywords: Inheritance; Gharawain; Mother's Inheritance Rights